The Interactions of Nutrition and Sleep Quality Focus on Melatonin Synthesis: A literature Review - Erma Wahyu Mashfufa; Ranti Kurnia Sari; Navy Sealsi Adinda Prisca Marina; Nur Aini; Lilis Setyowati; Ollyvia Freeska Dwi Marta (STIKep PPNI Jawa Barat, 2022)
Aim: Nutrition plays a role as a provider of energy for the human body which is important for the formation and maintenance, especially to improve the quality of sleep seen from the production of the hormone melatonin. The purpose of this study was to determine the interaction of nutrition on sleep quality: the focus synthesis of melatonin. Design: We performed a literature review study by reviewing 6 international journals related to the interaction of nutrition and sleep quality: focused on melatonin synthesis. Methods: Data collection was done by searching for data-based articles or journals published through the Willey Online Library, PMC, Proquest, and Pubmed. The data were analyzed by descriptive analysis and the journals were assessed using JBI. Results: The interaction of nutrition and sleep quality is seen from the hormone melatonin, based on the results of 6 journals. The results were described that the relationship between macronutrient and micronutrient nutrition on melatonin production that affects human sleep quality. Conclusions: Macronutrients and micronutrients are related to sleep quality in increasing the production of the hormone melatonin.